Sanksi Pidana Terhadap Tindak Pidana Pertambangan (Menurut Undang-Undang No. 4 Tahun 2009 Tentang Minerba) - I Made Bayu Sucantra; I Nyoman Sujana; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
Nowadays economic development is accompanied by increasingly advanced technological developments in Indonesia as a result of development causing various legal consequences. The growth of development is increasingly rapid and strong. Developmental development also has a role for the environment. This study aims to find out about the regulation of the management of mining business permits both requirements that must be met nationally and according to regional regulations. The application of criminal sanctions is carried out if there is a violation in the community of mining businesses that do not have a mining business permit that should be owned because it has been stated in Law Number 4 of 2009 and especially in Bali Regional Regulation Number 4 of 2017 as regulated permits and sanctions against mining. This study uses a normative approach. The data sources used are primary data, and secondary data. The problem in this thesis is the regulation of business permits for the mining of sandstone in Bali and the application of sanctions to perpetrators of unauthorized mining. The results of the study can be concluded that the form of regulation of mining business permits is regulated in Law No. 4 of 2009 concerning Mineral and Coal Mining and if you wish to have, the requirements are in the form of administrative requirements, technical requirements, environmental requirements, and financial requirements and for mining business permit arrangements rocks in Bali are regulated in Governor Regulation No. 37 of 2018.